PENERAPAN ALAT PERAGA BONEKA DENGAN TEKNIK VENTRILOQUIST UNTUK PENINGKATAN PEMAHAMAN SISWA DALAM MATA PELAJARAN SEJARAH KEBUDAYAAN ISLAM - Maulana, Muhammad Aditya; Susanti, Ria; Washfiah, Khairul (STIT Ibnu Rusyd Tanah Grogot, 2023)
The ventriloquist technique is the use of abdominal sounds accompanied by dolls by having a certain character personality. This research departs from the background that the learning process of students experiences a lackof a pleasant learning atmosphere and it makes children bored. Especially in learning Islamic Cultural History which is notoriously boring, the application of puppet props with ventriloquist techniques in learning Islamic Cultural History is very necessary. This study aims to determine the application of puppet props with ventriloquist techniques in increasing students' understanding in MI Rakha Amuntai. The subjects in this study were class VI A MI Rakha Amuntai students totaling 3.3 people consisting of 15 men and 1.8 women. The executing subjects of action are researchers and teachers of the history of Islamic culture. The object in this study is puppet props. This research is a class action research, which is carried out in 2 cycles with each cycle consisting of 2 meetings and 4 stages, namely Planning, Implementation, Observation, and Reflection. This class action research was conducted in class VI A MI Rakha. Data collection in this study was carried out by observation, documentation, and tests. The results of this study showed thatthe increase in learning activities in cycle I was 55.71% (Sufficient) to 92.8% (Very Good) in cycle II. Astudent activity in cycle I is 52.5% (Enough) to 100% (Very Good) in cycle II. Hasil student learning from 30.30% (Sufficient) to 100% (Very Good) in cycle II. This study can be concluded that the application of puppet props with ventriloquist techniques can increase student understanding by marking student activity in learning and completeness scores have been achieved.